Transformative Transparency for Local Natural Resource Revenue Management - Primi Suharmadhi Putri (Nordia Geographical Publications)
Extractive sector transparency has emerged as an important policy tool in addressing resource-related challenges. However, the implementation of extractive sector transparency initiatives has not often had transformative impacts on the ground. The initiatives often fall short in increasing public knowledge of the sector and revenue management, and fail in enhancing public’s capacity to discipline powerholders' behaviors. This thesis proposes that for a transparency initiative to be transformative, it needs to move beyond information disclosure and focus on the state-citizen interaction in natural resource revenue management. In this thesis, transformative transparency refers to a mechanism that simultaneously makes salient information available for the targeted citizen, promotes citizen action, and cultivates decision-maker sensitivity and responsiveness from the outset.